Continuous extension to the boundary of a domain of the logarithmic double layer potential - Plaksa, Serhiy Anatoliyovych (Eurasian Mathematical Journal, 2025)
For the real part of the Cauchy-type integral that is known to be the logarithmic potential of the double layer, a necessary and sufficient condition for the continuous extension to the Ahlfors-regular boundary is established. Sufficient conditions involving subclasses of Ahlfors-regular curves are also considered. Illustrative examples are presented.